2006
DOI: 10.1016/j.joca.2006.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Zonal variations in the three-dimensional morphology of the chondron measured in situ using confocal microscopy

Abstract: The shape and orientation of the chondron appear to reflect the local collagen architecture of the interterritorial matrix, which varies significantly with depth. Quantitative measurements of morphology of the chondron and its variation with site, disease, or aging may provide new insights into the influence of this structure on physiology and the pathology of articular cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 45 publications
3
111
0
1
Order By: Relevance
“…In fact, an electron microscopy study of the articular surface reported associations between ECM surface depressions and superficial cell groups in rabbit cartilage (Clark and Rudd, 1991). In addition, the local zonal collagen architecture appear to influence the chondron shape and orientation (Youn et al, 2006). Thus, specific patterns in the organization of superficial chondrocytes may be associated with the local articular surface structure.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, an electron microscopy study of the articular surface reported associations between ECM surface depressions and superficial cell groups in rabbit cartilage (Clark and Rudd, 1991). In addition, the local zonal collagen architecture appear to influence the chondron shape and orientation (Youn et al, 2006). Thus, specific patterns in the organization of superficial chondrocytes may be associated with the local articular surface structure.…”
Section: Discussionmentioning
confidence: 99%
“…Unfixed cartilage sections were labelled for type VI collagen, using a modified IF protocol [11]. At room temperature, sections were blocked for 20 min in 10 per cent normal donkey serum (lot no.…”
Section: Immunofluorescence For Type VI Collagenmentioning
confidence: 99%
“…Isolated chondrocytes also demonstrate zonal differences in their mechanical properties, with superficial zone cells exhibiting higher moduli than do middle/deep zone cells [32,33]. While the three-dimensional morphology and thickness of the PCM varies among the cartilage zones [11,14], micropipette aspiration of mechanically isolated chondrons from canine [34] and human [35,36] cartilage revealed zonal uniformity in the mechanical properties of the PCM, despite significant zonal differences in ECM properties. Although recent studies have evaluated the biomechanical properties of the cartilage PCM in situ indirectly using an inverse boundary element analysis coupled with three-dimensional confocal microscopy [37] and directly by atomic force microscopy (AFM) [38], the existence (or lack) of zonal variation in PCM properties in situ has yet to be determined.…”
Section: Introductionmentioning
confidence: 96%
“…The in situ geometry replicates the cell as an approximate prolate ellipsoid with major and minor diameters of 12 and 8 µm, respectively, where the major diameter is in a direction approximately perpendicular to the direction of loading. When modelled, the PC matrix was represented as 3-µm thick layer surrounding the cell membrane (Youn et al, 2006). The local EC region modelled around the cell extends 50 µm along the axial and radial directions, with the cell centred in this ROI.…”
Section: Study 2: Finite Element Analysis Of Cell Deformationmentioning
confidence: 99%